Apathy and affective symptoms associated with elevated plasma neurofilament light but not p-tau181 in Alzheimer's disease - Kang, Matthew J.Y.; Eratne, Dhamidhu; Loi, Samantha M.; Dang, Christa; Santillo, Alexander F. ; 0000-0001-9717-0820; Zetterberg, Henrik; Blennow, Kaj; Mitchell, Philip B.; Hopwood, Malcolm; Malpas, Charles B.; Velakoulis, Dennis (Alzheimer's and Dementia: Diagnosis, Assessment and Disease Monitoring, 2025)
INTRODUCTION: Apathy and affective neuropsychiatric symptoms (NPS) are prevalent in Alzheimer's disease (AD), yet their neurobiological cause is still unclear. We examined associations between plasma neurofilament light chain (NfL) and tau pathology (p-tau181) with apathy and affective symptoms in mild cognitive impairment (MCI) and AD dementia. METHODS: This longitudinal study analyzed data from 781 participants with MCI and AD dementia enrolled in ADNI, with annual blood samples collected over 4 years. NPS were assessed via the Neuropsychiatric Interview (NPI), and biomarker trajectories were analyzed using mixed-effects models. RESULTS: Elevated plasma NfL levels were associated with apathy, anxiety and depression in MCI and AD dementia, with apathy linked to a significantly higher rate of NfL increase, indicating accelerated neurodegeneration. DISCUSSION: Apathy and affective symptoms may indicate greater neurodegenerative burden in AD independent of tau-related pathology. Apathy was associated with a steeper rise in plasma NfL, suggesting a more aggressive disease progression. Highlights: Apathy and affective neuropsychiatric symptoms (NPS) are highly prevalent in clinical Alzheimer's disease (AD). The presence of apathy, depression or anxiety was associated with higher plasma levels of neurofilament light chain (NfL). Apathy was associated with an accelerated increase in plasma NfL levels over time. Apathy and affective NPS were not associated with p-tau181 levels in plasma.
Publisher Copyright: © 2025 The Author(s). Alzheimer's & Dementia: Diagnosis, Assessment & Disease Monitoring published by Wiley Periodicals, LLC on behalf of Alzheimer's Association.
Keywords: Alzheimer's disease; anxiety; apathy; blood-based biomarkers; depression; neurofilament light chain; neuropsychiatric symptoms; phosphorylated tau 181